Beyond Revascularization: Impact of Exercise-Based Cardiac Rehabilitation on Functional Capacity in ACS Complicated by Heart Failure – A Systematic Review and Meta-Analysis - Leoni; Ni Putu Ika Regina Maharani; Stefanus Leonardo Handoko; Ragil Nur Rosyadi (HM Publisher, 2026)
Background: Acute coronary syndrome (ACS) complicated by heart failure (HF) represents a distinct, high-risk phenotype. Even after successful revascularization via percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG), these patients remain vulnerable to maladaptive ventricular remodeling and functional decline. The role of exercise-based cardiac rehabilitation (CR) in this specific